Improvement of the operational Properties of sintered Copper steel through the use of an efficient alloying method - Pinchuk, S.Y.; Vnukov, O.O.; Kushnir, Yu.J.; Roslyk, I.G. (Наука та інновації, 2020)
Introduction. The alloying of powder steels, unlike cast steels, has a number of characteristic features due to the specifics of their preparation. The method of introducing the alloying component into the charge has a significant effect on the compactability, compressibility, structure and properties of sintered alloy steels. Problem Statement. Existing alloying methods often do not provide a uniform distribution of alloying elements over the volume of the powder mixture, which leads to uneven density and a decrease in the strength properties of sintered steel. Purpose. The purpose of research is to improve the technological properties of powder mixtures by using the most effective method for alloying sintered steels with copper Materials and Methods. As initial materials, we used sprayed iron powders of the ПЖР 3.200.28 grade (GOST-9849-86) and steel powder 70, which have low formability and green strength. A copper coating on iron powder particles was obtained by internal electrolysis (chemical cementation) in an acidic aqueous solution of copper sulfate with the addition of ferrous sulfate (II). Mechanosynthesis was carried out in a planetary ball mill. The technological properties of the powders were determined by standard methods: flowability ISO 4490, bulk density ISO 3923, compressibility ISO 3927, green strength ISO3995. Results. The research has been done in regard to the set of technological and physical properties of powder materials, as well as the mechanical characteristics and the structure of sintered construction materials obtained through the use of various technological methods of alloying with copper and carbon: mechanical mixing, mechanosynthesis and copperizing (chemical cementation). A comparative analysis the properties of the materials obtained has been carried out and the optimal alloying method has been determined. It has been established that powder materials alloyed using the chemical cementation method have the highest level of technological and mechanical characteristics. Conclusion. Chemical cementation alloying method can be recommended for the industrial production of sintered construction copper steels, since the use of it provides a high level of mechanical properties of the material and makes economic sense.